SEPSIS project: a protocol for studying biomarkers of neonatal sepsis and immune responses of infants in a malaria-endemic region. Issue 7 (23rd July 2020) - Fievet, Nadine; Ezinmegnon, Sem; Agbota, Gino; Sossou, Darius; Ladekpo, Rodolphe; Gbedande, Komi; Briand, Valerie; Cottrell, Gilles; Vachot, Laurence; Yugueros Marcos, Javier; Pachot, Alexandre; Textoris, Julien; et al.
Abstract : Introduction: Neonatal sepsis outreaches all causes of neonatal mortality worldwide and remains a major societal burden in low and middle income countries. In addition to limited resources, endemic morbidities, such as malaria and prematurity, predispose neonates and infants to invasive infection by altering neonatal immune response to pathogens. Nevertheless, thoughtful epidemiological, diagnostic and immunological evaluation of neonatal sepsis and the impact of gestational malaria have never been performed. Methods and analysis: A prospective longitudinal multicentre follow-up of 580 infants from birth to 3 months of age in urban and suburban Benin will be performed. At delivery, and every other week, all children will be examined and clinically evaluated for occurrence of sepsis. At delivery, cord blood systematic analysis of selected plasma and transcriptomic biomarkers (procalcitonin, interleukin (IL)-6, IL-10, IP10, CD74 and CX3CR1 ) associated with sepsis pathophysiology will be evaluated in all live births as well as during the follow-up, and when sepsis will be suspected. In addition, whole blood response to selected innate stimuli and extensive peripheral blood mononuclear cells phenotypic characterisation will be performed. Reference intervals specific to sub-Saharan neonates will be determined from this cohort and biomarkers performances for neonatal sepsis diagnosis and prognosis tested. Ethics and dissemination: Ethical approval has been obtained from the Comité d'Ethique de la Recherche – Institut des Sciences Biomédicales Appliquées (CER-ISBA 85 - 5 April 2016, extended on 3 February 2017). Results will be disseminated through international presentations at scientific meetings and publications in peer-reviewed journals. Trial registration number: ClinicalTrials.gov registration number: NCT03780712 .